2005
DOI: 10.1557/jmr.2005.0096
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous spark plasma synthesis and consolidation of WC/Co composites

Abstract: The single-step synthesis and densification of the WC-6Co cemented carbide starting from elemental powders was obtained by the spark plasma sintering (SPS) technique. The operating conditions that guarantee the complete conversion of the reactants to the desired full dense material have been identified. Specifically, under the application of 800 A and a mechanical pressure of 40 MPa for about 200 s, a product with relative density higher than 99%, hardness of 14.97 ± 0.35 GPa, and 12.5 ± 1.0 MPa m 0.5 fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…No systematic study has been reported on the partial substitution of WC by NbC in WC-Co hardmetals. To limit WC grain growth of WC-Co/Ni hardmetals, pressure assisted solid-state densification by means of pulsed electric current sintering (PECS) or spark plasma sintering (SPS) and hot pressing is reported to allow full densification of cemented carbides [5][6][7]. On the other hand, small additions up to 0.8 wt% of VC, Cr 3 C 2 or even NbC are widely used in WC-Co/Ni hardmetals to inhibit WC grain growth and to improve the oxidation and corrosion resistance [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…No systematic study has been reported on the partial substitution of WC by NbC in WC-Co hardmetals. To limit WC grain growth of WC-Co/Ni hardmetals, pressure assisted solid-state densification by means of pulsed electric current sintering (PECS) or spark plasma sintering (SPS) and hot pressing is reported to allow full densification of cemented carbides [5][6][7]. On the other hand, small additions up to 0.8 wt% of VC, Cr 3 C 2 or even NbC are widely used in WC-Co/Ni hardmetals to inhibit WC grain growth and to improve the oxidation and corrosion resistance [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive SPS includes the synthesis and densification of materials in a single step and thus offers faster processing times. (24) In this study, reactive SPS was employed to synthesize SnO 2 -based samples, Sn 1−2x Sb x Zn x O 2 (x = 0, 0.01, 0.03, 0.05, 0.07). The samples were prepared by reactive SPS followed by thermal treatment at a temperature of 1123 K. The temperature dependences of the electrical conductivity and Seebeck coefficient of the samples were measured from about 330 to 1073 K. The maximum TE power factor of 1.2×10 −4 Wm −1 K −2 was obtained at 1060 K for the x = 0.05 sample.…”
Section: Introductionmentioning
confidence: 99%
“…28 It is worth noting that SPS typically enables a compact to be sintered under more uniform heating conditions, lower temperature and relatively shorter sintering periods, as compared with conventional methods. 29,31 In particular, the latter two aspects allow grain growth to be minimized. 26,[29][30][31][32][33] Along these lines, in this work barium titanate powders obtained by SHS and mechanically treated to reach the desired nanostructure, are then densified by SPS apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…29,31 In particular, the latter two aspects allow grain growth to be minimized. 26,[29][30][31][32][33] Along these lines, in this work barium titanate powders obtained by SHS and mechanically treated to reach the desired nanostructure, are then densified by SPS apparatus. The influence of SPS time on densification, crystallite size and transition phase evolution is systematically investigated in this paper.…”
Section: Introductionmentioning
confidence: 99%